2015
DOI: 10.1115/1.4031580
|View full text |Cite
|
Sign up to set email alerts
|

Subject-Specific Carpal Ligament Elongation in Extreme Positions, Grip, and the Dart Thrower's Motion

Abstract: This study examined whether the radiocarpal and dorsal capsular ligaments limit end-range wrist motion or remain strained during midrange wrist motion. Fibers of these ligaments were modeled in the wrists of 12 subjects over multiple wrist positions that reflect high demand tasks and the dart thrower's motion. We found that many of the volar and dorsal ligaments were within 5% of their maximum length throughout the range of wrist motion. Our finding of wrist ligament recruitment during midrange and end-range w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…Ligaments were defined by finding origin and insertion sites that minimized the change in length of the ligament across the measured range of motion. In vivo evidence for the validity of isometric ligaments was recently supplied by Rainbow and colleagues, who found that selected capsular ligaments elongate minimally relative to their maximum length as the wrist moved through a large range of motion (Rainbow et al, 2015).…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Ligaments were defined by finding origin and insertion sites that minimized the change in length of the ligament across the measured range of motion. In vivo evidence for the validity of isometric ligaments was recently supplied by Rainbow and colleagues, who found that selected capsular ligaments elongate minimally relative to their maximum length as the wrist moved through a large range of motion (Rainbow et al, 2015).…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Although the SCCT has not been widely adopted as an accepted explanation of carpal mechanics, this concept was the basis of the ANAFAB reconstruction and the impetus to create a repair construct by combining selected components of existing repairs. An important reason for the SCCT not being widely accepted is that it fails to accord with the works of others (Kamal et al., 2016; Rainbow et al., 2016). Given that a reliable repair option for scapholunate instability has been elusive (Garcia-Elias, 2013; Sammer and Shin, 2012), an alternative approach, such as the one based on the SCCT, may be a potential new solution.…”
Section: Discussionmentioning
confidence: 99%
“…The stable central column of the carpus requires the motion of the lunate to be controlled and to resist its natural tendency to rotate into extension (Rainbow et al., 2015). As the lunate does not have any direct tendon connections, this stability can be achieved by an anterior tether pulling proximally and, in particular, the long radiolunate ligament (Sandow et al., 2014), acting with a presumed posterior tether pulling distally.…”
Section: Discussionmentioning
confidence: 99%
“…This study has integrated data from four NIH‐funded computed tomography (CT)‐image based in vivo studies on the wrist and thumb kinematics . The database used in this study has been also made freely available through SimTk.org (https://simtk.org/projects/carpal-database).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, our group published a database of in vivo carpal kinematics and anatomy for 60 healthy wrists . We postulate that expanding the database with additional studies would provide a more complete picture of carpal kinematics. In this study, our first aim was to assemble and describe an expanded open‐source database of in vivo wrist motions from 120 previously studied wrists.…”
mentioning
confidence: 99%